Análisis de la implementación de la política pública del seguro obligatorio de accidentes de tránsito-(SOAT), caso: Hospital de Especialidades Eugenio Espejo 2013-2014 - Chávez Montenegro, Richard Eduardo (2015)
The present research on the Analysis of Public Policy Implementation of Compulsory Traffic Accident Insurance-(SOAT) case: Specialty Hospital Eugenio Espejo, 2013-2014, aims to propose an alternative solution to overcome shortcomings in the implementation presented SOAT insurance in our country. The objective of this research is focused on analyzing the internal and external factors in the implementation of the policy taking into account the perspective of the users or beneficiaries, collaborators Hospital object of the case study, both public insurance and private sectors authorized to operate in the field SOAT, the bodies responsible assurance system and social groups representing citizens of the country, the results obtained from the researcher reflect the current state in which the implementation is SOAT of public policy in the national referral hospital. To obtain the results of field research techniques, closed-ended surveys aimed at users or relatives of people who suffered traffic accidents to personnel working in the institution providing health service already used specific personnel performing their activities in the admission, care, claims and recovery values of patients who have suffered vehicular accidents; likewise directed interviews of representatives of the actors involved in the system guarantee and the Ministry of Public Health, Insurance, Collective and Social Authorities Specialty Hospital Eugenio Espejo, in order to gain a broad understanding on the implementation of the policy SOAT in the country.